Prevalences of betel nut chewing and cigarette smoking among male prisoners before their imprisonment in Taiwan - Man-Line Chen; Kuei-Liang Yang; Hong-Sen Chen; Shu-Feng Shieh; Tien-Yu Shieh (Elsevier, 2012)
Background/purpose: Substance abuse is considered prevalent in incarcerated populations; however, consumption of betel nut in this group has not been adequately studied. In the present study, we attempted to elucidate the prevalences of betel nut chewing and cigarette smoking, and determine the relationship between use of the two substances among prisoners before imprisonment in order to increase our understanding of this phenomenon. Materials and methods: In 2000, a self-administered anonymous questionnaire was given to 976 male prisoners who were over 18 years of age and had been sentenced to imprisonment for a total incarnation period of more than 10 years in Kaohsiung Prison, Kaohsiung, Taiwan. Results: The response rate was 60.3% (589/976). Respective prevalences of betel nut chewing and smoking before imprisonment were 73.2% and 90.7%. Results of a cross-sectional analysis showed that dual-substance (betel nut and cigarette) users made up the majority (71.6%) of the study sample, whereas simple smokers and simple chewers comprised 19.0% and 1.5%, respectively. Only 7.8% of participants used neither substance. Smoking generally began 5.07 years before betel nut use. The duration of betel nut chewing was significantly associated with the daily quantity chewed (r=0.212; P<0.01), and a significant relationship was also found between the daily quantity chewed and smoking (r=0.314; P<0.01). Moreover, the daily quantity chewed increased concomitant with the chewing duration and daily quantity smoked. Conclusions: Prevalences of betel nut chewing and smoking are high among male Taiwanese prisoners before imprisonment. The association of use of these two substances among Taiwanese inmates was significant in a time-dependent manner.